The Patchwork of Land as a Problem Restricting the Development of Rural Areas - Karol Noga; Żanna Król (Barometr Regionalny, 2016)
The patchwork of land is one of the main factors negatively affecting agricultural production. Lands located in the external patchwork can be fully used for agricultural production, but the production costs are higher, and the income from the farm is smaller. The spatial layout of individual land in villages has undergone continuous changes over the centuries, which has led to their defectiveness through the occurrence of fragmentation and scattering of plots, the lack of access or large distances from the farm house. The article presents a detailed study of the spatial layout of the individual land in 29 villages of the commune of Cyców, located in Łęczyński County, Lubelskie Voivodship. The subject of the research was the fragmentation of plots of individual owners, land layout, and scattering of cadastral plots. In this work the index of the external border shape for the analyzed village was also calculated. Regarding the fact that the shape of the village is one of the most difficult properties to measure in the research, the index of shape for each village was calculated by the use of the coefficient of the expansion of borders assuming a square as a model figure. Circumference of the actual village and its area were used for calculations. The sizes of land of local and external non-resident owners of the commune of Cyców were also presented in terms of area and number of plots and the number of owners.